2019
DOI: 10.1042/cs20180959
|View full text |Cite
|
Sign up to set email alerts
|

USP4 deficiency exacerbates hepatic ischaemia/reperfusion injury via TAK1 signalling

Abstract: Ubiquitin-specific peptidase 4 (USP4) protein is a type of deubiquitination enzyme that is correlated with many important biological processes. However, the function of USP4 in hepatic ischaemia/reperfusion (I/R) injury remains unknown. The aim of the present study was to explore the role of USP4 in hepatic I/R injury. USP4 gene knockout mice and primary hepatocytes were used to construct hepatic I/R models. The effect of USP4 on hepatic I/R injury was examined via pathological and molecular analyses. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As TLR-4-NF-κB pathway in KCs is a classical signalling pathway and is activated during liver IRI, which is the main reason for sterile inflammation and hepatocellular apoptosis [38], we also detected the impact of IL-4 on these in vivo and in vitro. IL-4 treatment suppressed the inflammatory response and cell apoptosis induced by IRI and LPS.…”
Section: Discussionmentioning
confidence: 95%
“…As TLR-4-NF-κB pathway in KCs is a classical signalling pathway and is activated during liver IRI, which is the main reason for sterile inflammation and hepatocellular apoptosis [38], we also detected the impact of IL-4 on these in vivo and in vitro. IL-4 treatment suppressed the inflammatory response and cell apoptosis induced by IRI and LPS.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, USP4 was reported to block inflammatory responses induced by TLR− NF-κB and IL-1R− NF-κB signaling pathways by targeting TRAF6 and TAK1 [35,36]. USP4 knockout mice displayed enhancement of TAK1-NF-κB mediated liver inflammation in a hepatic ischaemia/reperfusion model [54]. Consistent with these findings, we found that USP4 knockdown in lung cancer cells increased phosphorylation of RelA, which is essential for NF-κB activation, and enhanced both basal and stimulus-induced inflammatory cytokine production, including production evoked by TNF-α and TLR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse hepatic I/R injury model was constructed according to the classical method with some small modifications ( 4 , 14 , 15 ). Mice underwent fasting for 12 h before surgery and were given free access to drinking water.…”
Section: Methodsmentioning
confidence: 99%